2017
DOI: 10.1111/jcpe.12722
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of collagen matrix seal and collagen sponge on ridge preservation in combination with bone allograft: A randomized controlled clinical trial

Abstract: Collagen matrix seal and CS, when combined with FDBA, significantly minimized ridge resorption in all dimensions and maintained buccal soft tissue thickness in sockets with a buccal plate loss of <2 mm in comparison to previously reported findings recorded after tooth extraction without ARP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 49 publications
2
59
2
9
Order By: Relevance
“…Although several studies in the literature reported an association between hypertension and periodontal diseases [27][28][29], we found that subjects with reported hypertension, who were living in areas where median household income was high, having lower bone loss compared to individuals who were living in areas where median household income was low. This is also supporting to the observation that individuals with high household income experienced lower difference in mean bone loss, which may indicate that access to healthcare system plays an important role by reducing the adverse effect of the outcome even among individuals who have predisposing conditions that put them at higher risk of the disease [30][31][32][33][34][35]. Nevertheless, limitations exist in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Although several studies in the literature reported an association between hypertension and periodontal diseases [27][28][29], we found that subjects with reported hypertension, who were living in areas where median household income was high, having lower bone loss compared to individuals who were living in areas where median household income was low. This is also supporting to the observation that individuals with high household income experienced lower difference in mean bone loss, which may indicate that access to healthcare system plays an important role by reducing the adverse effect of the outcome even among individuals who have predisposing conditions that put them at higher risk of the disease [30][31][32][33][34][35]. Nevertheless, limitations exist in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Measurement of the change in MBMV would have been desirable, but was beyond the scope of this study. CT grafting could have resulted in an increase in the peri‐implant soft‐tissue volume, which possibly compensated for the bone resorption–inducing effect of flap elevation in all the study groups. Only the last item in the PES, judging root convexity, soft‐tissue texture, and color, focuses on changes in soft‐tissue volume.…”
Section: Discussionmentioning
confidence: 99%
“…The natural repair response of an intact socket after tooth extraction is composed of bone resorption and neoformation (Devlin & Ferguson, ). In order to increase the predictability of implant therapy and esthetic outcomes, different techniques using a variety of materials were used to limit alveolar ridge resorption following tooth extraction (Araújo & Lindhe, ; Araújo, Silva, Misawa, & Sukekava, ; Barone et al, ; Jung et al, ; Meloni et al, ; Nart et al, ; Natto et al, ; Scheyer et al, ). A recent systematic review (Avila‐Ortiz, Chambrone, & Vignoletti, ) evaluating radiographic outcomes found a significant reduction in the vertical ridge resorption, while the horizontal resorption was inconsistent.…”
Section: Introductionmentioning
confidence: 99%